Umysł i życie — rzecz o pewnym dialogu dla zdrowia emocjonalnego - Kossakowski, Radosław (Kultura i Społeczeństwo, 2006)
The text relates to the attempt of constructing the common framework for the development of positive emotions by the world of science and buddhism. Scholars and buddhists (including the XIVth Dalai Lama) are trying to draw upon the practical and theoretical output of both traditions within the Mind and Life Institute conference. As a result of such dialogue we witness the emergence of therapeutic programs using the techniques of buddhist meditations (various traditions of this religion) in psychological clinics as well as pain and stress management centers. Buddhist meditation may complement rich plethora of methods used by western psychologists.